Living Qur’ân: Fadhîlah Surah al-Mulk dalam Tafsir Ibnu Katsîr (Kajian terhadap Tradisi dalam Membaca Surah al-Mulk Ba’da Maghrib di Pondok Pesantren Dârul ‘Ulûm Muara Mais Jambur Kabupaten Mandailing Natal) - Muhammad, Muhammad; Indra, Ahmad Perdana; Halimah, Halimah (Universitas Islam Negeri Sumatera Utara, 2020)
Alquran is the word of Allah which contains teachings and life guidance for Muslims. Such a function makes the students of the Islamic Boarding School Dârul 'Ulûm Muara Mais Jambur in Mandailing Natal Regency carry out the tradition of reciting Surah al-Mulk every day after performing the Maghrib prayer in congregation. This tradition is a suggestion from H. Mawardi Lubis Addary, the Headmaster (Mudîr) of the Islamic Boarding School. This tradition has a very positive value and deserves to be preserved. Therefore, the author considers it important to write a study entitled